Phosphors by Design: Approaches Toward the Development of Advanced Luminescent Materials. (1st January 2015) - Hermus, Martin; Brgoch, Jakoah
Abstract : The rapid discovery of new phosphors is necessary to enhance the next generation of solid-state lighting by improving device color quality and decreasing cost. This article reviews key non-conventional methods used to expedite novel phosphor discovery. The methods reviewed (with selected examples) include experimental methods such as combinatorial screening, and combined experimental and computation-based methods such as genetic-algorithm-assisted combinatorial chemistry and certain multi-objective optimization processes, and sophisticated stand-alone computational design processes that employ methods such as DFT. Key descriptors (such as Debye temperature) to be evaluated by computation are identified and their correlation to important properties are outlined.